Sperm cryopreservation and artificial insemination at Groote Schuur Hospital. - Wiswedel, Klaus (Department of Obstetrics and Gynaecology, 2017)
The diagnosis and therapy managed by the specialities of infertile couples is traditionally of Gynaecology and Andrology. The latter is a subspeciality, which should combine the knowledge of urologists and gynaecologists in the treatment of sub or infertile men.